Experience in employment and meaning of independent living among adults with learning difficulties - Wan Abdullah, Wan Arnidawati (Nova Science, 2020)
Participation in open employment is deemed as a means to independent living for the majority of persons with disabilities. However, the experience of being independent could have resulted differently for persons with learning difficulties who joined the labour market. Thus, it is substantial to understand the real meaning of ‘independence’ for persons with learning difficulties by exploring their life experiences after joining open employment. This study examined the knowledge and perspectives of persons with learning difficulties who joined integrated employment and linked the resulting changes brought about to their personal and social lives. Twenty-three persons with learning difficulties aged between 20 to 35 years old working in the retail sector in Malaysia participated in focused group interviews. A thematic analysis was conducted, and the themes connected to the markers of adulthood -biological, cognitive, emotional, role transitions, and responsibilities- to relate to the meaning of independent living. Findings suggest that the most explicit description of their personal and social lives is their dependency on parental support. Besides, their limitation to deal with everyday tasks also contributes to the ambiguity of independence. Despite having secure employment and are biologically adequate to be viewed as an adult, most of them are still far from stepping forward and leading their lives independently. Besides, the beliefs and cultural values also do shape the social construction of independence among persons with learning difficulties. Hence, it is essential to develop healthier surroundings to empower them to achieve meaningful lives.